RELATION BETWEEN DIETARY HABITS AND ANTHROPOMETRIC AND VASCULAR PARAMETERS IN CHILDREN ATTENDING THE PRIMARY SCHOOL. (June 2018) - Giontella, A.; Tagetti, A.; Bonafini, S.; Bresadola, I.; Minuz, P.; Principe, L. Nicolussi; Maffeis, C.; Antoniazzi, F.; Fava, C.
Abstract : Objective: Since childhood, unhealthy dietary habits could trigger the onset of cardiovascular risk factors, such as obesity and hypertension. Aim of this school-based study was to identify the possible relation between dietary patterns, physical activity and anthropometric, hemodynamic (blood pressure, BP; pulse wave velocity, PWV) and gluco-lipid parameters. Design and method: A validated Food Frequency Questionnaire (FFQ) and a validated questionnaire assessing the degree of physical activity (PAQ-C) were administered to children attending the 3rd and 4th class of 4 primary schools. Children responded with the aid of their parents and a dedicated dietitian. From FFQ, composed by 15 categories for a total of 61 foods, nutritional content in term of energy and macro-nutrients intake was extrapolated. Also dietary patterns obtained by Principal Component Analysis (PCA) were identified. Metabolic Equivalent of Task (MET) were computed for each child from IPAQ. Results: hree-hundred and nine children between 8 and 11 years participated (74, 8% response rate) of whose 302 (97, 7%) children compiled the FFQ. Significant correlations were found between: "junk food" intake and BMI (rs = 0.141, p < 0.05), diastolic BP (rs = 0.114, p < 0.05); PWV (rs = 0.155, p < 0.001), triglycerides (rs = 0.150, p < 0.05); meat intake and diastolic BP (rs = 0.124, p < 0.05); vegetables intake and Z-score of diastolic BP (rs = −0.115, p < 0.05); "animal fats" intake and cholesterol (rs = 0.165, p < 0.05). PCA identifies three dietary patterns: one characterized by junk food, meat, sweet, cereals and tubers; one composed by fruits, vegetables and fish and legumes and one characterized by eggs. No significant correlation was found between physical activity and the analyzed parameters. Conclusions: The significant correlation between some categories of food and anthropometric, vascular and gluco-lipid parameters in 8-11y children suggests that it is important to begin early with politics to prevent the onset of overt cardiovascular risk factors.